A Bacterial Toxin Perturbs Intracellular Amino Acid Balance To Induce Persistence - Xiaofeng Zhou (American Society for Microbiology, 2021)
To overcome various environmental challenges, bacterial cells can enter a physiologically quiescent state, known as dormancy or persistence, which balances growth and viability. In this study, we report a new mechanism by which a toxin-antitoxin system responds to harsh environmental conditions or nutrient deprivation by orchestrating a dormant state while preserving viability.